Religious perspective of doctor-patient relationship models in complementing uprising social phenomenal demands (ICETSR-35) - Sharifudin, Mohd Ariff; Wan Husin, Wan Rumaizi; Taib, Mai Nurul Ashikin (2014)
Recently several of the previously-accepted medical treatments have been questioned by the public. One of the factors highlighted is the uprising of social demands influenced by religious- centred ideation. Even though medical practitioners are regarded as one of the noble professions in society, their professional opinions are started to be questioned. To complement this social phenomenon, we reviewed and construct models of doctor-patient relationships from the religious perspective, Islamic law in particular. Most discussions related to doctor-patient relationship focused on codes of conducts such as medical ethics, professionalism, and confidentiality. In this brief review, we would like to highlight more on the models of doctor-patient relationship and the Islamic rulings related to it. The rulings were reviewed from various aspects pertaining to the patient who seeks for treatments, the doctor who provides the medical services or treatment, involvement of a third party, and the form of agreement involving all related parties. The rulings were derived from the five basic rules pertaining to the actions and interactions of a person (al- ahkam al-taklifiyyah). Relationship models were classified based on the profitability of the service rendered, types of contract involved, as well as the related Islamic rulings. The obligation of becoming a medical practitioner varies depending on various factors. Similarly, the rulings on patients seeking for treatment for medical illnesses remain debatable among religious scholars. Models of doctor-patient relationship can be summarized into four models; Model A - Charitable Work, Model B - Profit-based, Model C - Civil Servant, and Model D - Private Employee. Providing medical services is indeed a noble obligation. However, it involves certain requirements and principles in relation to the religious rulings that may differ from what are commonly practiced.